Analysis of the Effect of Taxpayer Compliance Supervision, Tax Audit and Tax Collection on Tax Revenue at KPP Pratama Banjarmasin - Muhammad Iqbal; Muhammad Ramadhan; I Gede Putu Suardana (Sean Institute, 2023)
The purpose of this study was to obtain empirical evidence that taxpayer compliance monitoring activities, tax audits and tax collection have a significant effect on tax revenue. The research was conducted at KPP Pratama Banjarmasin on corporate taxpayers during the 2019-2022 tax year. With purposive sampling method, a total of 6,492, 7,355, 8,208 and 9,548 taxpayers were obtained for each year from tax year 2019 to 2022. With statistical data analysis, multiple linear regression tests were carried out, classical assumption tests consisting of normality tests, autocorrelation tests, multicolonierity tests and heteroscedasticity tests and statistical model tests including the coefficient of determination test (R test), model feasibility test (F test) and hypothesis testing (t test). This study shows that partial taxpayer compliance and tax audits have a significant effect on tax revenue while tax collection has no significant effect on tax revenue. Simultaneously all variables have a significant effect on tax revenue.